2020
DOI: 10.1136/ijgc-2019-000980
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism among patients receiving neoadjuvant chemotherapy for advanced epithelial ovarian cancer

Abstract: ObjectivesNeoadjuvant chemotherapy may be considered for women with epithelial ovarian cancer who have poor performance status or a disease burden not amenable to primary cytoreductive surgery. Overlap exists between indications for neoadjuvant chemotherapy and known risk factors for venous thromboembolism, including impaired mobility, increasing age, and advanced malignancy. The objective of this study was to determine the rate of venous thromboembolism among women receiving neoadjuvant chemotherapy for epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Our group has shown that chemotherapy treatment is an independent risk factor for VTE in gynaecological cancer patients [7]. In a recent study, BMI, cancer stage and histological subtype were not found to be predictive of increased VTE risk in patients undergoing neoadjuvant chemotherapy, further highlighting the need for a greater understanding of the prothrombotic mechanisms involved in chemotherapy associated thrombosis [6]. The pathogenesis of chemotherapy associated thrombosis, particularly in the neoadjuvant setting, is unclear but a combination of tumour burden and treatment related factors are likely to be involved.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our group has shown that chemotherapy treatment is an independent risk factor for VTE in gynaecological cancer patients [7]. In a recent study, BMI, cancer stage and histological subtype were not found to be predictive of increased VTE risk in patients undergoing neoadjuvant chemotherapy, further highlighting the need for a greater understanding of the prothrombotic mechanisms involved in chemotherapy associated thrombosis [6]. The pathogenesis of chemotherapy associated thrombosis, particularly in the neoadjuvant setting, is unclear but a combination of tumour burden and treatment related factors are likely to be involved.…”
Section: Introductionmentioning
confidence: 95%
“…The cornerstone of ovarian cancer treatment is cytoreductive surgery followed by adjuvant chemotherapy, however patients who cannot be optimally debulked are frequently treated with neoadjuvant chemotherapy followed by interval debulking surgery which further exacerbates VTE risk. High rates of VTE have been reported in ovarian cancer patients who undergo neoadjuvant chemotherapy [6]. In addition, ovarian cancer patients who experience a VTE during neoadjuvant chemotherapy having a longer mean time to surgery.…”
Section: Introductionmentioning
confidence: 99%
“…1 VTE is a complication in pathology or pregnancy and can lead to a high death rate. 2,3 This disease is the major cause of death among cancer patients accounting for 9% of all maternal deaths. 4,5 In-patients can increase the risk of DVT by 10–40% without any prevention, and even reach 60–80% in orthopedics wards.…”
Section: Introductionmentioning
confidence: 99%
“…Six included studies encompassing 718 patients reported on the prevalence of VTE in ovarian cancer patients undergoing chemotherapy [ 40 , 79 , 82 , 96 , 115 , 121 ]. The meta-analysis revealed a pooled estimated prevalence of 8%, ranging from 5% to 12% (ES 8%; 95% CI 5–12%; z = 7.47; p = 0.02) ( Table 4 and Supplemental SI Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%